Advanced Vocabulary - Götz, Dieter; Mittmann, Brigitta (Linguistische Dimensionen des Fremdsprachenunterrichts, 2005)

A method for finding and assessing differences in lexical clusters and cluster frequencies between spoken British and American English - Mittmann, Brigitta (Proceedings of the Ninth EURALEX International Congress, EURALEX 2000, Stuttgart, Germany, August 8th-12th, 2000, Vol. II, 2000)

Collocation in English dictionaries at the beginning of the twenty-first century - Herbst, Thomas; Mittmann, Brigitta (Lexicographica, 2008)
UnivIS-Import:2015-03-09:Pub.2008.phil.daa.iaa.lali.colloc

Comparing British and American conversations: Routine formulae, linguistic and cultural differences - Mittmann, Brigitta (Linguistics and Cross-Cultural Communication: Present, Past and Future. International Scientific Conference, 2004)

Contrasting valency in English and German - Mittmann, Brigitta (Valency: theoretical, descriptive, and cognitive issues, 2007)
Keywords: Valency; contrastive linguistics

Dictionary Skills. Das Workbook zum DCE - Herbst, Thomas; Mittmann, Brigitta; Kucharek, Richard; Heath, David (Langenscheidt-Longman, 1997)
UnivIS-Import:2015-04-02:Pub.1997.phil.daa.iaa.lali.dictio

Editorial: Constructions under construction: Items, patterns, grammar - Klotz, Michael; Mittmann, Brigitta; Sanchez-Stockhammer, Christina; Uhrig, Peter (Yearbook of the German Cognitive Linguistics Association, 2023)

How can American English and British English Be Recognised? Arguments in Favour of Shifting the Focus in the Study of Language Varieties Toward(s) Use and Reception - Herbst, Thomas; Mittmann, Brigitta (Cultural Encounters in the New World. Literatur- und Kulturwissenschaftliche Beiträge zur kulturellen Begegnung in der Neuen Welt, 2003)
UnivIS-Import:2015-04-20:Pub.2003.phil.daa.iaa.lali.howcan
Keywords: pronunciation; accent; perception; foreign language teaching

'I almost kind of thought well that must be more of like British English or something' – Prefabs in amerikanischer und britischer Konversation - Mittmann, Brigitta (Linguistische Dimensionen des Fremdsprachenunterrichts, 2005)

Lexikografie, ihre Basis- und Nachbarwissenschaften. (Englische) Wörterbücher zwischen 'common sense' und angewandter Theorie - Herbst, Thomas; Lorenz, Gunter; Mittmann, Brigitta; Schnell, Martin (Niemeyer, 2004)
UnivIS-Import:2015-07-08:Pub.2004.zwiss.sz.sz5.lexiko

Mehrwort-Cluster in der englischen Alltagskonversation. Unterschiede zwischen britischem und amerikanischem gesprochenen Englisch als Indikatoren für den präfabrizierten Charakter der Sprache - Mittmann, Brigitta (Gunter Narr Verlag, 2004)
The importance of fixed or semi-fixed multi-word expressions such as routine formulae, lexicalised sentence stems or frequent collocations has increasingly been recognized over the past two decades. Considering this surge of interest in lexical combinatorics, it is surprising that very little has been published on British-American variation in this field. So far, the literature on differences between American and British English has mostly ignored word combinations.     The book is a thorough and extensive study of this central field of English dialectology. It is based on two computerized corpora of English conversation: the ‘spoken demographic’ part of the British National Corpus (BNCSD) and the Longman Spoken American Corpus (LSAC). All age groups, all major social strata and a variety of different regions of the two countries are represented in both corpora. Both are similar in size: the LSAC has about 4.9 million words of running text, while the BNCSD contains about 3.9 million words.     A series of programs specially written for this purpose by a computer programmer was used to extract the most frequent word combinations (or clusters) from each of the two corpora, to count their frequency of occurrence, and to select those which are the most frequent and most typical for each of the two varieties. Thus, the method is neutral and does not restrict or anticipate the results in any way. It works very well with an investigating study of the kind described here.     The study showed that British and American speakers of English differ considerably with respect to many word combinations which they typically use very frequently. The clusters reveal interesting phenomena on all levels of linguistic description. In most cases, the word combinations studied here are not restricted exclusively to one of the two varieties, but there are usually strong tendencies for them to occur predominantly in either American or British English. A number of these differences between the varieties have been noted in passing by other researchers, but many of them should be new.     Most of the highly frequent word combinations are conversational routines or parts of them. They range from greeting and thanking formulae to hedges, discourse markers and general extenders. Frequent multi-word expletives can also be considered to be types of routine formulae.     A large number of clusters points to what one might call the ‘fuzzy edges’ of phraseology. On the borderline between phraseology and syntax there are, for example, tag questions, periphrastic constructions such as the present perfect, semi-modals, and valency patterns. On the borderline between phraseology and word formation, on the other hand, there are adjectival combinations consisting of participle and particle, as well as complex prepositions, conjunctions, adverbs, or pronouns.     Only a small part of the material has to do with what one might consider to be ‘classical idioms’, but the corpora contain many other pre-assembled multi-word chunks that function as linguistic building blocks. Some items (such as the reporting construction BE like) are indeed idiomatic in character. Others – like time adverbials or recurrent responses – are not generally regarded as fixed expressions so that their formulaic character may come as a surprise. Even they fall within the scope of phraseology.     Traditionally, phraseology is mostly concerned with idioms. However, it is necessary to widen the scope of what is studied in this field. This means including not only routine formulae, support verb constructions and word combinations such as phrasal and prepositional verbs, but also other kinds of prefabricated expressions.     The British-American differences reported on in this study provide further proof for the fact that everyday language is to a great extent conventionalised. It consists largely of ready-made chunks consisting of several words which are presumably stored in the speaker’s memory as entities. Thus, idiomaticity pervades language.     On the whole, the research carried out here suggests that claims concerning linguistic manifestations of differences in national character should indeed be challenged. In particular, Algeo’s assumption that there is a “greater tendency of British to qualify and make tentative its statements” is not supported by the material contained in the corpora.     The methodology used in the study is also described in: Brigitta Mittmann (2000): “A method for finding and assessing differences in lexical clusters and cluster frequencies between spoken British and American English”, in: Heid, U. (et al.) (eds): Proceedings of the Ninth EURALEX International Congress, EURALEX 2000, Stuttgart, Germany, August 8th-12th, 2000, Vol. II, Universität Stuttgart: IMS, 579-590.
Keywords: Clusters; Multi-wort-units; Corpus-based; Prefabs; British English; American English; spoken English

New tendencies in the treatment of collocations - Mittmann, Brigitta (Dictionaries: An International Encyclopedia of Lexicography. Supplementary Volume: Recent Developments with Focus on Electronic and Computational Lexicography, 2013)
Keywords: collocations; dictionaries; Kollokationen; Wörterbücher

Pragmatik und Wörterbücher: Präfabrizierte Einheiten der gesprochenen Sprache - Mittmann, Brigitta (Lexikografie, ihre Basis- und Nachbarwissenschaften, 2004)

Prefabs in spoken English - Mittmann, Brigitta (The phraseological view of language : a tribute to John Sinclair, 2011)

Review of: Geoffrey Leech, Marianne Hundt, Christian Mair and Nicholas Smith. Change in Contemporary English. A Grammatical Study - Mittmann, Brigitta (Zeitschrift fur Anglistik und Amerikanistik, 2011)

Review of: Henry Béjoint. The Lexicography of English From Origins to Present - Mittmann, Brigitta (Linguistische Berichte, 2011)

Review of: John Algeo. 2006. British or American English? A Handbook of Word and Grammar Patterns. (Studies in English Language.) Cambridge: Cambridge University Press - Mittmann, Brigitta (English World-Wide, 2008)

Rezension zu: Joybrato Mukherjee. English Ditransitive Verbs - Mittmann, Brigitta (Anglistik, 2006)

Strategies of fair lexicography - how present- day dictionaries of English show respect - Garibyan, Armine; Koroleva, Daria; Mittmann, Brigitta; Herbst, Thomas (Lexicographica, 2022)
This article investigates the ways in which present-day monolingual dictionaries of the English language show respect towards groups of people. On the basis of the analysis of selected entries of the most recent editions of English learners' dictionaries and the Concise Oxford Dictionary we outline five different strategies employed in these dictionaries to avoid discrimination of and offensiveness towards other people. The analysis comprises the phrasing of definitions, illustrations, the selection of examples, the choice of headwords as well as usage notes in comparison to data obtained from English corpora.
CRIS-Team WoS Importer:2022-12-30

The treatment of collocations in OALD5, LDOCE3, COBUILD2 and CIDE - Mittmann, Brigitta (The Perfect Learner's Dictionary (?), 1999)
Keywords: collocations; dictionaries

Vorwort: Zwischen common sense und angewandter Theorie - Herbst, Thomas; Lorenz, Gunter; Mittmann, Brigitta; Schnell, Martin (Lexicographica, 2004)

With a little help from 'Friends' (and others): Lexico-pragmatic characteristics of original and dubbed film dialogue - Mittmann, Brigitta (Anglistentag 2005, Bamberg – Proceedings, 2006)
Keywords: film transcript; corpus analysis